Knowledge-based adaptive frequency control of gas turbine generator model for multi-machine power system / Hidayat Zainuddin and Slobodan Jovanovic - Zainuddin, Hidayat; Jovanovic, Slobodan (UiTM Press, 2008)
This paper investigates the performance of a knowledge-based supplementary control to enhance the quality of frequency control of gas turbine generator for multi-machine case of one area of interconnected power system. The proposed Intelligent Gas Turbine Controller (IGTC) uses acceleration feedback to counter the over and under frequency occurrences due to major disturbances in power system network. Consequently, generator tripping and load shedding operations can be reduced. In addition, this type of controller is integrated with Automatic Generation Control (AGC), a well known LoadFrequency Control (LFC) in order to ensure the system frequency is restored to the nominal value. Computer simulations of frequency response of each gas turbine governing system are used to optimize the proposed control strategy. As a result, there is substantial improvement on the system frequency represents the speed of the equivalent generator of multimachine system that employing the proposed control strategy.